A case of Dentigerous Cyst in Association of Impacted Mandibular Canine - Gupta, Gaurav; Gupta, Dinesh Kumar; Gupta, Priyanka; Gupta, Neelja; Rana, Kuldeep Singh (Journal of Orofacial Research, 2018)
Dentigerous cyst being the second most common odontogenic cyst which constitutes around 20-24% of all the odontogenic cysts involving the jaws. Usually, these cysts remain asymptomatic and rarely cause enlargement and displacement of associated tooth. It develops by an accumulation of fluid between reduced enamel epithelium and the tooth crown of an unerupted tooth. This case report presents conservative treatment modality for 17-year-old female patient, diagnosed with a dentigerous cyst in association of impacted mandibular canine. The patient was treated with a minimal invasive approach, enucleation followed by marsupialization under local anesthesia, preserving all the teeth in occlusion.